Integrating Ecosystem Vulnerability in the Environmental Regulation Plan of Izmir (Turkey)—What Are the Limits and Potentialities? - Stefano Salata; Sıla Özkavaf-Şenalp; Koray Velibeyoğlu (Urban Science, 2022)
The land-use regulatory framework in Turkey is composed of several hierarchical plans. The Environmental Regulation Plan pursues comprehensive planning management, which ranges between 1/100,000 and 1/25,000 and defines the framework for local master plans. Unfortunately, there is scarce knowledge of how these plans effectively protect the environment. Besides, these plans have poor consideration of socio-economic dynamics and the ecosystem vulnerability, while evaluating the actual conflicts or synergies within the localization of ecological conservation and settlement expansion areas. In this work, an ecosystem-based geodatabase was created for the western Izmir area (Turkey). The dataset has been created by employing a supervised classification sampling of Sentinel-2 images acquired on 28 March 2021, while accessing ONDA-DIAS services to L2C products. Then, the InVEST software was used to map the Habitat Quality and the Habitat Decay, while the ArcMap raster analysis tool was employed to generate the Normalized Difference Vegetation Index. The results were used to classify the ecosystem vulnerability of the western metropolitan area of Izmir and then superimposed to the Environmental Regulation Plan of the city of Izmir (2021), thus evaluating synergies and conflicts. Although integration of the ecosystem services approach into spatial planning is lacking in the planning practice of Turkey, the paper provides an operative methodology to integrate ecosystem evaluation in environmental planning as a basic strategy to support sustainable development.